Education Leadership in Challenging Situations - A Case Study of UNRWA Schools in The Gaza Strip - Almassri, Ivan (Trinity College (Dublin, Ireland). School of Education, 2022)
The effects of the COVID-19 pandemic in particular and the challenging situations of conflict in Gaza Strip on the continuity to access quality, inclusive and equitable education with the increasingly volatile situation during the blockade in Gaza, have imposed school closure and remote or distance learning and teaching and have also imposed challenges on school principals leading and managing schools during such unexpected times. This research examines the impact COVID-19 has had on teaching, learning, and leading UNRWA schools and investigates the challenges that the school principals encountered at the seven dimensions of Education Senior Management, School Leadership and Management, Teachers, Students, Infrastructure and Technical Equipment, Curriculum and Parents. The research briefly looks at the period from March to September 2020-2021 scholastic year and the return to school in August 2021. Chapter One provided an introduction, background, aims and objectives, rationale, and the structure of this research project. Chapter Two presents literature that draws on the example of education in conflict, drawing on the Gaza-Strip as the illustrative case study. Chapter Three outlines the research methods used along with an explanation of how the data was correlated. A variety of qualitative and quantitative findings are presented in Chapter Four. Chapter Five provides a discussion of the findings extracted from both the qualitative and quantitative research methods used. Chapter Six provides a recap of the research process and on foot of the research provides a series of recommendations. As an education practitioner and a leader at UNRWA Gaza Education Programme and witnessing four conflicts of 2008, 2012, 2014 and 2021 and as a front liner during COVID-19, the researcher realized the importance of linking her experience and practice to the theories of education leadership and management in emergencies. In the researcher's point of view, education in emergencies response cycle should be contextualized by adapting the Inter-agency Network for Education in Emergencies (INEE) Minimum Standards to Gaza Strip local context by involving parents and community, adaptive teaching-learning processes, teacher development, curriculum, students' assessment, psychosocial support, inclusive education approach and finally data, monitoring, and evaluation.
Keywords: Educational Leadership and Policy; Education